Implementasi Smart Room Pada Ruangan Very Important Person (VIP) Berbasis Internet of Things (IoT) - Arvan, Muhammad Haekal; Puteri Novani, Nefy; Hadelina, Rizka (Universitas Andalas, 2025)
The development of an Internet of Things (IoT)-based smart room system in a Very Important Person (VIP) room was carried out using a NodeMCU ESP8266 microcontroller, a Passive Infrared (PIR) sensor, and the Blynk application. The system is capable of detecting human presence at a distance of up to 5 meters with a detection angle of 35°-145°, and automatically controlling electronic devices such as lights and music players. Additional manual control is carried out through the Blynk application for volume and equalizer settings. Testing shows that the system successfully reduces electricity consumption by turning off devices when no users are present. The PIR sensor detection success rate reached 98% in a 7 x 4 meter room, with a system response time of less than 2 seconds. The system also supports light control through two methods: input from the PIR sensor and the Blynk application. The overall implementation demonstrates operational efficiency, ease of management, and potential energy savings in an IoT-based VIP room facility.